2016
DOI: 10.1128/aac.02011-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Features of Decreased Chlorhexidine Susceptibility among Nosocomial Staphylococcus aureus Isolates at Texas Children's Hospital

Abstract: One of the strategies utilized to decrease infections in the hospital setting relies on topical antimicrobials and antiseptics. While their use is beneficial, concerns arise over the potential to develop resistance or tolerance to these agents. We examined nosocomial Staphylococcus aureus isolates from 2007 to 2013 for the presence of genes associated with tolerance to chlorhexidine. Isolates and patients were identified from an S. aureus surveillance study at Texas Children's Hospital. Nosocomial S. aureus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 46 publications
1
43
2
Order By: Relevance
“…In S. aureus, the smr gene and the qacA/B gene complex have been associated with elevated MICs and minimum bactericidal concentrations (MBCs) of CHG. A number of investigators have discovered an increase in the incidence of organisms bearing these genes following widespread use of CHG in hospital units (12)(13)(14) and, more rarely, following exposure to CHG outside the hospital setting (15,16). Importantly, the presence of these genes has been associated with resistance to other systemic antimicrobial agents, including clindamycin and ciprofloxacin (smr), as well as higher MICs of vancomycin (qacA/B) (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In S. aureus, the smr gene and the qacA/B gene complex have been associated with elevated MICs and minimum bactericidal concentrations (MBCs) of CHG. A number of investigators have discovered an increase in the incidence of organisms bearing these genes following widespread use of CHG in hospital units (12)(13)(14) and, more rarely, following exposure to CHG outside the hospital setting (15,16). Importantly, the presence of these genes has been associated with resistance to other systemic antimicrobial agents, including clindamycin and ciprofloxacin (smr), as well as higher MICs of vancomycin (qacA/B) (17,18).…”
mentioning
confidence: 99%
“…The impact of the use of these agents on the development of genotypic or in vitro CHG resistance has been minimal in large clinical trials of CHG-based decolonization regimens (15,19). Previous studies of children have shown an association between antiseptic tolerance genes in S. aureus and the presence of central venous lines (CVLs), as well as a higher rate of invasive infection (18). Many previous pediatric studies, however, have been biased by including high-risk populations, such as neonates/infants and oncology and cardiac surgery patients (12,18,20,21).…”
mentioning
confidence: 99%
“…Third, the intervention period was relatively short (18 months), and results may not be generalizable to longer periods of routine decolonization. Fourth, we looked for only two efflux pump genes; other efflux pumps that can use CHG as a substrate have been described in S. aureus (18,35).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced susceptibility to CHG in MRSA occurs via efflux, and identification of plasmid-mediated genes, such as qacA and qacB, that encode multidrug efflux pumps has been considered genotypic evidence of CHG nonsusceptibility by some (16,17). However, the relationship between the carriage of multidrug efflux pump genes and decreased susceptibility to CHG is inconsistent; phenotypic susceptibility has been demonstrated in MRSA strains that carry qacA or qacB, and reduced susceptibility has been reported in strains that lack these or other multidrug efflux pump genes (15,(18)(19)(20). The inconsistency may be due in part to the ability of the pump encoded by qacA, but not that encoded by qacB, to utilize CHG as a substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation